ROLE OF MULTIDETECTOR CT SCAN IN EVALUATION OF CORONARY ARTERY BYPASS GRAFTS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Acute myocardial infarction (AMI) is the leading cause of death for both sexes in industrialised countries. Almost 50% of all patients with coronary artery disease (CAD) die of an AMI without warning signs. Coronary atherosclerosis is shown as coronary CAD. The narrowing of the coronary artery lumen reduces blood and oxygen flow to the heart, leading to myocardial ischaemia. A unique medical success story is surgical revascularisation for atherosclerotic heart disease. The operation has been developed to relieve angina following revascularisation, improve exercise tolerance and provide survival advantages.